A novel method of using indocyanine green fluorescence technique for nephron-sparing surgery - Rishi Nayyar; Chandan J. Das; Prashant Gupta (Indian Journal of Urology)
Two complex small renal masses were operated using a novel method of utilising indocyanine green fluorescence for nephron-sparing surgery (NSS), overcoming its current limitations of short duration of effect and non-enhancement of the tumor. The dye was emulsified with ethiodized oil and a 1:1 mixture was administered on the morning of the surgery using superselective cannulation of the direct tumoral blood supply. The fluorescence could be used throughout the entire course of the surgery irrespective of arterial clamping, allowing quick tumor identification, edge marking, and near-enucleation over enucleoresection. This novel method has the potential to aid the surgeon during various critical steps of NSS.